Serum lactates and acute kidney injury in patients with sepsis: A cohort analysis - Miguel Gonçalves; Joana Gameiro; Marta Pereira; Natacha Rodrigues; Iolanda Godinho; Marta Neves; João Gouveia; Zélia Costa e Silva; Sofia Jorge; José António Lopes (Cogent Medicine, 2017)
Granting the association of lactates with mortality has been largely documented in critically ill patients with sepsis, its association with the development of acute kidney injury (AKI) in this setting is not well established. We aimed to analyze the association of serum lactates at intensive care unit (ICU) admission with the occurrence AKI in a cohort of critically ill septic patients. Materials and methods: This study is retrospective including 457 adult patients with sepsis admitted to the Division of Intensive Medicine of the Centro Hospitalar Lisboa Norte (Lisbon, Portugal) between January 2008 and December 2014. The Kidney Disease Improving Global Outcomes (KDIGO) classification was used to diagnose and classify patients developing AKI within the first week of hospitalization. Logistic regression analysis was employed to determine factors associated with AKI development. Data were expressed as odds ratios (ORs) with 95% confidence intervals (CIs). Statistical significance was defined as a p-value < 0.05. Results: AKI occurred in 87.5% of patients with a maximum KDIGO category (19.5% with stage 1, 22.6% with stage 2 and 45.4% with stage 3). Serum lactates were higher among patients developing AKI as compared with non-AKI patients (mmol/L 29.9 ± 25.7 vs. 18.6 ± 9.3, p = 0.001; unadjusted OR 1.04 (95% CI 1.02–1.07), p = 0.001; adjusted OR 1.03 (95% CI 1.01–1.06), p = 0.024), and they were progressively higher in accordance with AKI severity (stage 1, 24.5 ± 18.7; stage 2, 25.5 ± 16.9; stage 3, 34.6 ± 30.7; p = 0.001). Conclusions: Serum lactates at ICU admission were independently associated with the occurrence of AKI in critically ill patients with sepsis.